MENINGKATKAN KEMAMPUAN MENGENAL HURUF VOCAL MELAUI MEDIA PUZZLE BAGI ANAK KESULITAN BELAJAR KELAS II DI SDN 18 KOTO LUAR - Genesa Vernanda, Markis Yunus, Rahmatrisilvi (Universitas Negeri Padang, 2013)
The research on the back by the second grade Gifted students in SDN 18 Koto Luar, for proving puzzle media can improve children recognize letters for learning difficulties at 18 Koto SDN Luar. This research uses experimental approach in the form of Single Subject Research (SSR) with a research design using ABA design. Media puzzle can improve cognitive ability vowel learning difficulties for children second grade at SDN 18 Koto Luar.